Effects of Different Pretreatments and Dark-Light Conditions on the Seed Germination of Different Mulberry Species - Gunes, Mehmet; Cekic, Cetin (Asian Journal of Chemistry, 2016)
The research was carried out to determine the seed germination of four different mulberry species. The seeds were exposed to the following treatments prior to germination: scarification with absolute H2SO4; H2SO4 + 1000 ppm GA3 application; soaking in water for 24 h; GA3 application in concentrations of 1000, 2000 and 4000 ppm for 24 h. The seeds sown in petri dishes containing two sheets of filter paper were incubated at 25 ± 1°C in dark and light conditions. Most pretreatments, except in one or two cases, significantly enhanced the seed germination of all mulberry species. Full germination was obtained from all concentrations of GA3 for white and red mulberries and from 2000 ppm and 4000 ppm concentrations for pendulous mulberry. Treatment of 1000 ppm GA3 resulted in greater germination in black mulberry among the treatments. Germination did not occur in watersoaked and control seeds of black mulberry at the end of three weeks. The result of this study showed that the darkness had a positive effect on the germination rate as well as germination percentage.